Beyond the pandemic: understanding the perceived changes in mental health of the elderly population - Herdian, Herdian; Septiningsih, Dyah Siti; Estria, Suci Ratna; Nuryana, Zalik; Yuniawati, Rudy; Tarnoto, Nissa (International Journal of Public Health Science (IJPHS), 2024)
This study aimed to describe the mental health of the elderly before and after the COVID-19 outbreak using a qualitative approach. Ten elderly people volunteered to participate in offline semi-structured interviews. The data was analyzed using the interpretative phenomenological analysis (IPA) technique. The results of our study mentioned the differences in the mental health of the elderly during the COVID-19 outbreak and after the COVID-19 outbreak. The elderly felt the difference in emotional terms, such as being more relieved and happier because activities returned to normal. The elderly feel calmer when using religion as religious coping to overcome psychological problems that arise during the COVID-19 outbreak. During the COVID-19 outbreak, elderly people still working also feel the impact on the family's economy, which compounds the problem. Excessive coverage on social media also helped make the elderly more afraid of COVID-19. The study's results can help improve older people's mental health after COVID-19 by understanding their experiences and finding good ways to cope. It suggests that future research should look at specific ways to support older people's mental health, taking into account their special challenges and the role of social media in causing fear and worry about COVID-19.